PENINGKATAN KEMAMPUAN PEMEBELAJARAN MENULIS PARAGRAF ARGUMENTASI MENGGUNAKAN METODE SAINTIFIK (Di Kelas X SMK Negeri 9 Kabupaten Tangerang) - Rifaatussalwa Hayati; Zakiyatul Mardiyah (Universitas Tangerang Raya, 2022)
The purpose of this study was to describe the process of learning to write argumentative essays, to describe the improvement of argumentative essay writing skills, and to describe changes in the behavior of students in class X-Ak2 SMK N 9 Tangerang Regency. The research in this research is classroom action research using the Krutt Lewin method. Learning is developed by selecting and using lesson plans, media, methods, and evaluations to improve school quality. The results of this study indicate an increase in argumentative essay writing skills in the initial condition test, the first cycle test, and the second cycle test. In the pre-cycle test, students obtained an average score of 68.1, while in the first cycle, the student's test results reached an average of 70.8. Based on this, there was an increase of 2.7 or 3.96%, namely from 68.1 in the initial condition to 70.8 in the first cycle. In the second cycle, the average value achieved was 81.67 and was included in the good category. , so that there was an increase of 10.87 or 15.35%, from 70.8 in the first cycle to 81.67 in the second cycle. The results of the second cycle test, showed that from 30 students, 20 students were declared complete and 10 students had not completed because they had not reached the KKM score of 75. The percentage of completeness reached 66.67%, this indicates that the target of student completion is more than 50% of students. finished. So this proves the success of researchers in research writing argumentative essays using the scientific method.